An Analysis of Floating Maxim in â€œIt Ends With Usâ€ Movie: Qualitative Research - Tazkiyatul Wildaniyah; Astuti Mu'ammalatun; Siti Novia Ade Putri; Irma Khoirot Daulay; Toyyibah Toyyibah (Universitas Muria Kudus, 2025)
An adaptation of Colleen Hoover's novel,